COVID-19: Secure Healthcare Internet of Things Networks, Current Trends and Challenges with Future Research Directions - Adil, Muhammad; Ali, Jehad; Jadoon, Muhammad Mohsin; Alotaibi, Sattam Rabia; Kumar, Neeraj; Farouk, Ahmed; Song, Houbing (ACM Transactions on Sensor Networks, 2023)
The number of affirmed COVID-19 cases showed an enormous increase in the recent past throughout the globe. Keeping in view the catastrophic destruction of this devastating virus, there is a must-need situation to maximize the use of existing healthcare technologies such as the healthcare Internet of Things (H-IoT). In healthcare, patient wearable devices are widely recognized as a dormant technology with enormous capabilities to assess and combat various diseases, e.g., cough, seizure, temperature, heartbeat, and so on. As we know, in the H-IoT, patient-wearable devices are dispersed in an infrastructure-free environment that exposes them to several private and public coercion while accumulating and transmitting high sensitive data over the wireless communication channel. Therefore, security is the main concern of these applications, and thus, the primary focus of this article to outline the limitations and challenges in the present literature from 2019 to 2021, to identify the requirements of H-IoT applications used in the context of COVID-19. Following this, we will move one step ahead to explore the current security techniques adopted in these applications. Consequently, we will identify the network architectural, cryptographic, protocols, and operational security challenges during our study to recommend viable research directions and opportunities, which could be helpful and capable to minimize the network architecture, deployment, and maintenance cost with more productive outcomes.
Keywords: 'current; Authentication of patient wearable device; COVID-19 and healthcare IoT application; Future research directions; Healthcare IoT application; Healthcare technology; Seizure temperature; Sensitive datas; Wearable devices; Wireless communication channels; authentication of patient wearable devices; COVID-19 and healthcare IoT applications; Data privacy; healthcare IoT applications